The professionalization of teaching practices from the teaching philosophy - García Zárate, Ma. de Lourdes (Emerging Trends in Education, 2024)
The professionalization of teaching practices is a priority issue for society, since the quality of the educational service offered to students depends on it. There have been various proposals to advance in this area, for example, cascade training, courses, evaluation systems, etc. However, there is still much to do, according to (Coppola 2002) one way to professionalize the teacher is through his teaching philosophy where he expresses how he believes his students learn a subject, which implies a reflective exercise that requires accompaniment. But how the teacher learns to teach, in this research 19 teaching philosophies of primary school teachers enrolled in a master's program were analyzed to identify the learning theory in which their teaching practices were located. The methodological proposal consisted of a content analysis to code them, then analyze them from a methodical reading and interpret them from the learning theories of (Pozo, 2006). The results show that the methodological proposal allows to identify the learning theory where the teacher is, the finding is that teachers can find themselves in evolution migrating from one theory to another.
Keywords: teacher professionalization; teaching philosophies; learning theories